Qualidade do sono de idosos institucionalizados : a prática de massagem como terapia alternativa - Eidelwein, Lauana Davila (2015)
The process of human aging can generate modifications in the quality and in the quantity of the sleep, with a negative impact in the health of elderly population. The massage has the adjunct role in the health development, and it can be used as alternative therapy in the treatment of problems related to the sleep. Objective: To assess the effects of the massage in the sleep quality of elderly residents in long-stay institutions. Method: It is a longitudinal, interventional, non-randomized and controlled study, from crossover type, without blinding, which has included, initially, ten elderly patients in the intervention group and seven patients in the control group. The intervention group has received a treatment with massage during one month, eight sections for thirty minutes, and twice a week. After the washout period, the crossover has occurred between the groups. The quality of the sleep of the elderly and the possibility of them taking a nap in everyday situations, before and after the intervention, were analyzed considering the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESS). To verify the difference between the average of the numeric variables, it was used the T-student test, considering 0.05 significance level. The project was approved by the Research Ethics Committee from Universidade de Passo Fundo, Rio Grande do Sul, Brazil, under number 892.725, and it contemplates the Resolution 466/12, from National Health Council, Ministry of Health. Results: Seventeen elderlies with average age of 81.5 (DP: 8.3) participated of the study, 64.7% (equivalent to eleven elderly people) were female, 88.2% (fifteen elderly people) have incomplete Elementary School, 70.6% (twelve elderly people) are single, widowers or separated. After the interventions, it was observed an improvement in the quality of the sleep of elderlies who have presented, initially, the quality of the sleep as bad, with a diminution of the percentage in more than 23.3%; however, there was no difference with the ones who expressed, from the beginning, sleep disturbances. Conclusion: The results have showed that the treatment with massage did not improve the sleep quality of elderly people with sleep disturbances. However, it has improved for those with a bad sleep quality. It is suggested, thus, new researches to assess in a more suitably way the effects of the massage in the quality of the sleep